OUTDOOR SETTING IN TEACHING SPEAKING ENGLISH (RETAIN, 2017)
OUTDOOR SETTING IN TEACHING SPEAKING ENGLISH Khoirul Arifin Engish Literature, Faculty of Language and Arts, The State University of Surabaya khoirul.arifin85@yahoo.com Prof. Susanto, M.Pd. English Literature, Faculty of Language and Arts, The State University of Surabaya susantoniki@gmail.com ABSTRACT Getting ability in communication orally is the main priority of learning English. Therefore, the successfulness of learning English is measured when having ability in speaking English well. To be able to cover this, there are some principles of teaching English which must include in teaching and learning English. Commonly, teaching and learning speaking are conducted inside classroom in indonesia. Otherwise, there was a teacher of a school that was applying outdoor setting to conduct teaching and learning speaking English. In the other hand, outdoor setting commonly, was to conduct teaching and learning that focused on building joyful learning or science. Therefore, it was nescessary to conduct research to investigate in what way outdoor setting help the teacher to conduct teaching and learning speaking process. This research aimed to describe (1) how outdoor setting helped teacher to deliver speaking materials (2) how outdoor setting helped teacher to conduct teaching and learning strategies and (3) how outdoor setting helped teacher to stimulate students in learning speaking English. The research design was descriptive and the approach was qualitative. The observations were done in the class that the phenomena happened. The data was taken from both verbal and non-verbal activities and then it was in the form of fieldnotes. After collecting the data by observing the class, the data was analysed to get interpretation then report the result. Based on the result of the research, the outdoor setting helped the teacher in three aspects. Those are delivering material, conducting teaching and learning strategies and stimulate students to participate actively in the learning process. The previous aspects were the aspects that the teacher could do by applying outdoor setting during teaching and learning process. Keywords : outdoor setting, speaking ABSTRAK Mendapat kemapuan dalam berkomunikasi secara lisan ada prioritas utama dalam belajar bahasa inggris. Maka dari itu keberhasilan belajar bahasa inggris diukur ketika mempunyai kemampuan dalam berbicara bahasa inggris dengan baik. Untuk mencapai hal tersebut, ada beberapa landasan dalam mengajar bahasa ingris yang harus terdapat proses belajar dan mengajar bahasa ingris. Pada umumnya, proces mengajar dan belajar speaking dilakukan di dalam kelasa di indonesia. Sementara itu ada seorang guru dari sebuah sekolah yang menerapkan setting outdoor dalam menyampaikan belajar dan mengajar speaking inggris. Disisi lain, umumny outdoor setting digunakan untuk mengajar atau belajar yang fokus pada membangun proses belajar yang menyenangkan atau saint. Maka dari itu, penting untuk melakukan penelitian untuk mengetahui bagaimana cara outdoor membantu guru dalam menyelenggarakan proses belajar mengajar speaking ingrris. Penelitian ini bertujuan untuk mendeskripsikan 1) bagaimana outdoor setting membantu guru dalam mencapaikan materi speaking. 2). Bagaimana outdoor setting membantu guru dalam menjlankan strategi mengajar dan belajar dan 3) bagaimana outdoor setting membantu guru dalam merangsang siswa untuk belajar speaking inggris. Design penelitihan ini adalah deskriptive dan pendekatannya adalah kualitative. Observasinya dilakukan pada kelas yang fenomenanya terjadi pada kelas tersebut. Datanya diambil dari aktifitas verbal maupun non verbal dan kemudian diwujudkan dalam bentuk fieldnote. Setelah mengumpulkan data dengan cara observasi kelas tersebut, data tersebut dianalisa untuk interpretasi dan laporan hasil penelitian. Berdasarkan hasil dari penelitian, outdoor setting membantu guru dalam tiga aspek. Yaitu adalah penyampaian materi, pelaksanaan strategi belajar dan mengajar dan merangsang siswa untuk berpartisipasi aktif dalam proses belajar. Aspek – aspek berikut adalah aspek yang guru dapat lakukan dengan menerapkan outdoor setting selama proses mengajar dan belajar. Kata Kunci : outdoor setting, speaking